Enhancing students' motivation and understanding: a study using YouTube-based learning in IPAS - Siti Amna, Nuril Huda, Sunardjo (Lembaga Bale Literasi, 2025)
Along with the development of technology, digital media such as YouTube has become an effective alternative in improving the quality of learning in the classroom. However, the use of YouTube as a learning medium for science still requires further study. This study aims to determine the effect of YouTube-based learning on student motivation and understanding in the subject of IPAS (Natural and Social Sciences) in grade V students at SDN Sukolilo Barat 2 Labang Bangkalan. This research is based on students' low interest and understanding of IPAS material delivered conventionally. Through a quantitative approach with a pre-experimental research design, students were given IPAS material through learning videos uploaded on the YouTube platform. The results of MANOVA on learning motivation and understanding of material in class V SDN Sukolilo Barat 2 Labang show a significance value of 0.000 which is smaller than the value of ? = 0. 05 (0.000 < ? = 0.05) so that based on the assessment, there is an effect of YouTube-based by utilization on learning motivation and understanding of material in class V students at SDN Sukolilo Barat 2 Labang Bangkalan.